Rearrangements of the retinoic acid receptor alpha and promyelocytic leukemia zinc finger genes resulting from t(11;17)(q23;q21) in a patient with acute promyelocytic leukemia. - Chen, S J (1993)
Cytogenetic study of a patient with acute promyelocytic leukemia (APL) showed an unusual karyotype 46,xy,t(11;17) (q23;21) without apparent rearrangement of chromosome 15. Molecular studies showed rearrangements of the retinoic acid receptor alpha (RAR alpha) gene but no rearrangement of the promyelocytic leukemia gene consistent with the cytogenetic data. Similar to t(15;17) APL, all-trans retinoic acid treatment in this patient produced an early leukocytosis which was followed by a myeloid maturation, but the patient died too early to achieve remission. Further molecular analysis of this patient showed a rearrangement between the RAR alpha gene and a newly discovered zinc finger gene named PLZF (promyelocytic leukemia zinc finger). The fusion PLZF-RAR alpha gene found in this case, was not found in DNA obtained from the bone marrow of normals, APL with t(15;17) and in one patient with AML-M2 with a t(11;17). Fluorescence in situ hybridization using a PLZF specific probe localized the PLZF gene to chromosomal band 11q23.1. Partial exon/intron structure of the PLZF gene flanking the break point on chromosome 11 was also established and the breakpoint within the RAR alpha gene was mapped approximately 2 kb downstream of the exon encoding the 5' untranslated region and the unique A2 domain of the RAR alpha 2 isoform.